2007
DOI: 10.1007/978-1-59745-395-0_17
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Spontaneous Autoimmune Disease

Abstract: The nonobese diabetic (NOD) mouse represents probably the best spontaneous model for a human autoimmune disease. It has provided not only essential information on type 1 diabetes (T1D) pathogenesis, but also valuable insights into mechanisms of immunoregulation and tolerance. Importantly, it allows testing of immunointervention strategies potentially applicable to man. The fact that T1D incidence in the NOD mouse is sensitive to environmental conditions, and responds, sometimes dramatically, to immunomanipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 151 publications
0
20
0
Order By: Relevance
“…Previous reports have shown that most of NOD/ShiLtJ mice become diabetic between 12 and 16 weeks of age, and the development and onset of the type-1 diabetes is accelerated upon PD-L1 blockade3760. We therefore monitored the urine glucose levels in mice during the course of anti-PD-L1 treatment and found that they remained normal in all the mice throughout the experiments.…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have shown that most of NOD/ShiLtJ mice become diabetic between 12 and 16 weeks of age, and the development and onset of the type-1 diabetes is accelerated upon PD-L1 blockade3760. We therefore monitored the urine glucose levels in mice during the course of anti-PD-L1 treatment and found that they remained normal in all the mice throughout the experiments.…”
Section: Discussionmentioning
confidence: 92%
“…We then tested whether the development of diabetes in NOD mice, a well-established type 1 diabetes model (26), is preceded by changes in the level of miRNAs in pancreatic islets. In NOD mice, peri-insulitis begins around a few islets 6–8 weeks after birth and characterizes a majority of islets at the age of ∼13–14 weeks (27).…”
Section: Resultsmentioning
confidence: 99%
“…Because FAS is regulated by insulin in lipogenic tissues (37), we showed that FAS protein was decreased in the hearts of two insulin-deficient models, streptozotocin-treated mice and animals with K ATP -induced neonatal diabetes (17,38), and in the hearts of an insulin-resistant model, db/db mice (Fig. 1, A-C) (39).…”
Section: Cardiac Fas and Generation Of Faskardmentioning
confidence: 95%